2269. HIV-Positive Individuals Who Report Being in Care Are Less Likely to Be Co-Infected With an STI; an Analysis of "Network Testing, " A Service Program Offering HIV and STI Testing Services to Individual at Risk for HIV. (26th November 2018) - Issema, Rodal; Songster, Tamika; Edgar, Mallory; Davis, Billy; Lee, Tabatha; Harris, James; Cleveland, Takisha; Chancler, Henry; Rosebush, Julia; Schneider, John
Abstract: Background: The prevalence of STIs among people living with HIV (PLWH) has implications for HIV treatment as prevention and community efforts to stop the spread of HIV. We explored the factors associated with HIV/STI co-infection in HIV-positive individuals. Methods: We analyzed data from our "Network Testing" service program, which was designed to expand HIV/STI testing services to high-risk individuals including gay, bisexual, and other men who have sex with men (MSM) in Chicago's South side, a high HIV prevalent area. This program provides incentivized testing to participants and up to six referred individuals within their social network. The prevalence of selected STIs, including syphilis, gonorrhea, or chlamydia infection, among HIV-positive individuals was evaluated. Bivariate and multivariable logistic regression analyses were used to assess sociodemographic, testing history, and risk factors significantly associated with HIV/STI co-infection. Results: Of the 295 HIV-positive individuals, 110 (37%) tested positive for at least one STI, with 90 (32%) testing positive for syphilis, 23 (16%) for gonorrhea, and 12 (8%) for chlamydia. The median age was 27 years old and 91% of clients were MSM. In multivariable analyses, individuals who reported being in care were less likely to be co-infected (adjusted odds ratio [aOR] 0.45, 95% confidence interval 0.23–0.90). Additionally, participants who reported having a previous STI test were more likely to be co-infected (aOR=6.10, 95% CI: 1.87–19.90). We found no association with co-infection and other risk factors including multiple partners and condomless sex. Conclusion: The high STI prevalence among HIV-positive individuals suggests: 1) a continued need for regular STI testing and treatment among PLWH to reduce the likelihood of HIV transmission to others; and 2) the receipt of HIV care serves as an important opportunity to provide comprehensive services including STI testing/treatment. Disclosures: R. Issema, CDC FOA PS15-1502: Employee of Grant Recipient and Employee, Grant recipient. CDC FOA PS17-1704: Employee of Grant Recipient, Grant recipient. T. Songster, CDC FOA 15-1502: Employee of the grant recipient, Grant recipient. CDC FOA 17-1704: Employee of grant recipient, Grant recipient. M. Edgar, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. B. Davis, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. T. Lee, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. J. Harris, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. T. Cleveland, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. H. Chancler, CDC FOA PS15-1502: Employee of Grant Recipient, Grant recipient. J. Schneider, CDC FOA PS15-1502: Grant Investigator, Grant recipient. CDC FOA PS17-1704: Grant Investigator, Grant recipient. Chicago Department of Public Health A2 HIV Prevention and Testing Grant: Grant Investigator, Grant recipient.